THE EFFECTS OF DIFFERENT STORAGE TEMPERATURES AND TIME ON THE SURVIVAL OF CPE (+) CLOSTRIDIUM PERFRINGENS TYPE A IN CIG KOFTE (A TRADITIONAL TURKISH RAW MEAT PRODUCT) - Guran, Husnu Sahan; Ilhak, Osman Irfan (Walter de Gruyter Gmbh, 2015)
This study was carried out to investigate the survival of cpe (+) Clostridium perfringens type A in cig kofte. For this purpose, cig kofte samples were artificially contaminated with the pathogen, and then the samples were stored at 4, 24 and 30 degrees C for 72 h. The numbers of cpe (+) Clostridium perfringens type A, total aerobic mesophilic bacteria (TAMB) and lactic acid bacteria (LAB) in the samples were analysed at 6, 12, 24, 48 and 72 h of storage. The number of the pathogen in the samples stored at 30 degrees C significantly decreased during the storage and dropped below detection level (10 cfu/g) after 48 h while the reduction number of the pathogen in the samples stored at 4 degrees C was 1.60 log cfu/g at the end of the 72 h. The numbers of the TAMB and LAB in the samples stored at 24 degrees C and 30 degrees C rapidly increased compared to the samples stored at 4 degrees C during the storage period (P<0.05). This study demonstrates that this pathogen can survive in cig kofte stored at refrigeration temperature for more than 3 days, but cannot survive at 30 degrees C for 3 days.
Keywords: cpe (+) C. perfringens type A; time; temperature; cig kofte; survival